2018
DOI: 10.1021/acs.jafc.7b05287
|View full text |Cite
|
Sign up to set email alerts
|

Using Fluorescence Spectroscopy To Identify Milk from Grass-Fed Dairy Cows and To Monitor Its Photodegradation

Abstract: Owing to its high ω-3 fatty acid content, milk from grass-fed dairy cows is becoming increasingly more attractive to consumers. Consequently, it is important to identify the origins of such products and to measure their content, at least relative to some standard. To date, chromatography has been the most extensively used technique. Sample preparation and cost, however, often reduce its widespread applicability. Here, we report the effectiveness of fluorescence spectroscopy for such quantification by measuring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Another explanation for the green color of our milk samples could be pigments like chlorophyll metabolites, including pheophorbide a . Bhattacharjee et al [ 40 ] demonstrated that commercial milk from grass-fed cows was richer in chlorophyll metabolites than milk from grain/silage-fed cows.…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation for the green color of our milk samples could be pigments like chlorophyll metabolites, including pheophorbide a . Bhattacharjee et al [ 40 ] demonstrated that commercial milk from grass-fed cows was richer in chlorophyll metabolites than milk from grain/silage-fed cows.…”
Section: Discussionmentioning
confidence: 99%
“…Each solution was placed in a dark room for 24 h to ensure the full extraction of the pigments to the solvent. The absence of light ensures that the chlorophyll in the solution does not undergo photodegradation 1 . In order to correct for variable water content in the frozen silage, for each sample, three portions of about 5 g per portion, from various areas of the frozen sample were ground to a homogeneous consistency, weighed and then placed in an oven to dry for 24 h in order to obtain a dry‐to‐wet mass ratio.…”
Section: Methodsmentioning
confidence: 99%
“…Our current investigation began as a consequence of a previous project 1 focusing on authenticating the grass‐fed label by analyzing chlorophyll catabolite 2 content in milk and correlating that to the cattle‐diet, specifically those which are either grass or derived from grass. These studies were carried out by measuring the fluorescence of chlorophyll and its derivatives 3–5 in the milk 1 . Detection of a strong signal from chlorophyll metabolites in the milk was suggested to be indicative of a grass‐fed diet.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given current awareness regarding product origin and traceability in the dairy industry, a rapid technique based on fluorescence and riboflavin could be useful in confirming product authenticity. Fluorescence has also been used to authenticate milk from grass-fed cows ( 89 ). The levels of riboflavin and chlorophyll metabolites were measured in the milk and shown to be significantly higher in grass-fed cows than in grain or silage-fed cows, most likely due to the higher level of chlorophyll in fresh grass.…”
Section: Spectroscopic Technologies and Their Usage In The Dairy Indu...mentioning
confidence: 99%